2005
DOI: 10.1021/om050402l
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Comparative η1-Alkyl and Sterically Induced Reduction Reactivity of (C5Me5)3Ln Complexes of La, Ce, Pr, Nd, and Sm

Abstract: The synthesis of (C 5 Me 5 ) 3 Ce and (C 5 Me 5 ) 3 Pr from [(C 5 Me 5 ) 2 Ln][(µ-Ph) 2 BPh 2 ] and KC 5 Me 5 completes the series of sterically crowded (C 5 Me 5 ) 3 Ln complexes for the larger lanthanides, La-Nd and Sm, and allows a comparison of structure and reactivity as a function of metal size. Synthesis of these new (C 5 Me 5 ) 3 Ln complexes required silylated glassware, which surprisingly was not necessary for the more sterically crowded analogues. (C 5 Me 5 ) 3 Ce and (C 5 Me 5 ) 3 Pr display longer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
157
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 129 publications
(167 citation statements)
references
References 102 publications
10
157
0
Order By: Relevance
“…The reactivity of (C 5 Me 5 ) 3 Gd vis-à-vis (C 5 Me 5 ) 3 Sm was of interest to determine whether the sterically more crowded complex of the smaller metal would have higher reactivity. Previously, it had been observed that the larger metals, La-Nd, which generate the less sterically crowded complexes, are less reactive than Sm (8). However, because Sm often has special reactivity because of the presence of its divalent state, Sm 2ϩ (2,11,12), it was important to examine the metal size͞reactivity relationship with both larger and smaller metals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reactivity of (C 5 Me 5 ) 3 Gd vis-à-vis (C 5 Me 5 ) 3 Sm was of interest to determine whether the sterically more crowded complex of the smaller metal would have higher reactivity. Previously, it had been observed that the larger metals, La-Nd, which generate the less sterically crowded complexes, are less reactive than Sm (8). However, because Sm often has special reactivity because of the presence of its divalent state, Sm 2ϩ (2,11,12), it was important to examine the metal size͞reactivity relationship with both larger and smaller metals.…”
Section: Discussionmentioning
confidence: 99%
“…Such syntheses required developing reactions that did not depend on the Sm(II) reactivity shown in Scheme 1. Successful syntheses of (C 5 Me 5 ) 3 Ln complexes of the larger metals, La (1.216 Å) (17) (8).…”
Section: T He Pentamethylcyclopentadienyl Ligand (C 5 Me 5 )mentioning
confidence: 99%
See 1 more Smart Citation
“…(4)]. [24] This result implies that the first step in SIR of [ 2 M] (M = Ca, Yb, Sm) crystallize isomorphously in space group P1 with the metal ion on the center of inversion (Figure 1). Considering the presence of many n-butyl substituents, the structures are surprisingly ordered and of good quality.…”
mentioning
confidence: 94%
“…This reactivity profile is novel as only a handful of Sm II complexes have previously been shown to promote oxalate product formation, [19,20] and CO 2 insertion into a Sm-ligand bond is rare. [19,28] In order to shed some light on this peculiar reactivity as well as to determine some plausible reaction pathways, DFT calculations (B3PW91) were undertaken on the reaction of 1 with CS 2 , CO 2 , and COS. The reaction with CS 2 was first investigated.…”
Section: Resultsmentioning
confidence: 99%